DISTRIBUTION OF COPEPODS IN THE NORTHERN BERING SEA AND THE CHUKCHI SEA IN OCTOBER 1988 (EXTENDED ABSTRACT) (Twelfth Symposium on Polar Biology) - ハットリ, ヒロシ; タニムラ, アツシ; フクチ, ミツオ; マツダ, オサム; HATTORI, Hiroshi; TANIMURA, Atsushi; FUKUCHI, Mitsuo; MATSUDA, Osamu (National Institute of Polar Research, 1991)
P(論文) departmental bulletin paper